Effects of antidepressant use during pregnancy on delivery mode, beginning of labor and birth outcome among women in Iceland - Telma Rún Ingadóttir 1996- (2020)
Women at the childbearing age are at a higher risk of developing depression compared to any other time in their lives. One of the effective treatments for depression is antidepressants. The prevalence of antidepressant use among pregnant women has been an important research topic around the world. Between 2008-2012, the use of antidepressants among pregnant women in Iceland was shown to increase by 1.5%. Studies have consistently shown that antidepressant use during pregnancy can increase risk for low birth weight, preterm delivery, cesarean section as well as induction of labor. Nevertheless, the effects of antidepressant use during pregnancy, on birth mode and neonatal outcomes, has not been examined in Iceland before. The current research aimed to study the effects of antidepressants on the mode of delivery, beginning of birth, and the condition of the newborn among women in Iceland. The participants were all women that gave birth to children at the national hospital Landspítalinn, from December 2018 to December 2019. The results of the study showed an increased risk of cesarean sections among the women who used antidepressants during pregnancy. Unexpectedly, there was no interaction found between delivery mode and antidepressant use neither on pregnancy length nor birth weight. Keywords: antidepressants, pregnancy, mode of delivery, birth weight, the beginning of birth, pregnancy length. Konur á barneignaraldri eru í aukinni áhættu á að greinast með þunglyndi samanborið við annan tíma í lífi þeirra. Þunglyndislyf er ein af þeim áhrifaríku meðferðum sem notaðar hafa verið við þunglyndi. Algengi notkunar þunglyndislyfja meðal barnshafandi kvenna hefur verið rannsóknarefni um allan heim um árabil. Á árunum 2008-2012 jókst notkun þunglyndislyfja meðal barnshafandi kvenna á Íslandi um 1,5%. Erlendar rannsóknir hafa endurtekið sýnt að notkun þunglyndislyfja á meðgöngu getur leitt til lægri fæðingarþyngdar, fyrirburafæðingar, aukinnar áhættu á keisaraskurði og auknar líkur á þörf fyrir framköllun fæðingar. Áhrif ...